Evaluating the Vertical Extension Module of a Building with Installed Rotary Dampers at Joints - Seokjae Heo; Seunguk Na; Moo-Won Hur; Sanghyun Lee (Buildings, 2021)
In this study, the shape of a vertical expansion module with a rotary-type damping device is proposed. The external energy dissipation capacity is confirmed through experiments and the performance of the module is simulated. It can be easily applied to high-rise structures, as the module is directly supported by the bearing walls without the need for a separate base system. Additionally, as the damper can be replaced, it is possible to enhance seismic performance even after construction. The simulation results show that the rotary-type damper is more effective in reducing the displacement, shear force, and moment than free and fixed joints. In the pushover analysis of a system modeled using the moment hinge of the rotary damper of the joint, the best response reduction effect is obtained when the yield moment of the hinge is defined as 1% of the frame plastic moment. As a result of the analysis of the multi-degree-of-freedom system considering a harmonic load, we determined that it is efficient for the hinge to yield after the displacement, and the acceleration response of the resonant structure reaches steady state during the installation. In the multi-degree-of-freedom system with slab joints added to the analytical model, the displacement response decreased gradually as the natural period of the structure decreased and the joint increased. This provides evidence that the damper does not affect the overall behavior of the structure. The most important design factor of the rotary-type friction damper, shown through the experiment, is the relationship between the frictional surface and the tightening force of the bolt.